The therapeutic efficacy of Bifidobacterium animalis subsp. lactis BB‐12® in infant colic: A randomised, double blind, placebo‐controlled trial. Issue 1 (3rd December 2019) - Nocerino, Rita; De Filippis, Francesca; Cecere, Gaetano; Marino, Antonio; Micillo, Maria; Di Scala, Carmen; de Caro, Carmen; Calignano, Antonio; Bruno, Cristina; Paparo, Lorella; Iannicelli, Anna M.; Cosenza, Linda; et al.
Summary: Background: The pathogenesis of infant colic is poorly defined. Gut microbiota seems to be involved, supporting the potential therapeutic role of probiotics. Aims: To assess the rate of infants with a reduction of ≥50% of mean daily crying duration after 28 days of intervention with the probiotic Bifidobacterium animalis subsp. lactis BB‐12 ® (BB‐12). Secondary outcomes were daily number of crying episodes, sleeping time, number of bowel movements and stool consistency. Methods: Randomized controlled trial (RCT) on otherwise healthy exclusively breastfed infants with infant colic randomly allocated to receive BB‐12 (1 × 10 9 CFU/day) or placebo for 28 days. Gut microbiota structure and butyrate, beta‐defensin‐2 (HBD‐2), cathelicidin (LL‐37), secretory IgA (sIgA) and faecal calprotectin levels were assessed. Results: Eighty infants were randomised, 40/group. The rate of infants with reduction of ≥50% of mean daily crying duration was higher in infants treated with BB‐12, starting from the end of 2nd week. No infant relapsed when treatment was stopped. The mean number of crying episodes decreased in both groups, but with a higher effect in BB‐12 group (−4.7 ± 3.4 vs −2.3 ± 2.2, P < 0.05). Mean daily stool frequency decreased in both groups but the effect was significantly higher in the BB‐12 group; stool consistency was similar between the two groups. An increase in Bifidobacterium abundance (with significant correlation with crying time reduction), butyrate and HBD‐2, LL‐37, sIgA levels associated with a decrease in faecal calprotectin level were observed in the BB‐12 group. Conclusions: Supplementation with BB‐12 is effective in managing infant colic. The effect could derive from immune and non‐immune mechanisms associated with a modulation of gut microbiota structure and function. Abstract : LINKED CONTENT This article is linked to Iacovou and Nocerino et al papers. To view these articles, visit https://doi.org/10.1111/apt.15599 and https://doi.org/10.1111/apt.15627 .